The Influence of Playdough Media on Visual-Spatial Intelligence of Group B Children (5-6 Years) - Amelia, Dini; Ilhami, Akmillah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of playdough media on visual spatial intelligence of group B children (5-6 years old) at Angkasa Lanud Kindergarten Palembang. This study used a pre-experimental method with a One Shot Case Study Design . The research sample consisted of 16 children selected using a purposive sampling technique . Data collection techniques include observation, testing and documentation. The data were analyzed using a one-sample t-test, which showed that the value of ? ?????? = 4.48 was greater than ? ????? = 1.75, so Ho is rejected and Ha is accepted. These results indicate that playdough media has a positive and significant effect on children's visual spatial intelligence. The implications of this study indicate that the use of playdough media not only improves children's visual spatial intelligence, but also develops fine motor skills, and cognitive and creativity in children.